2016
DOI: 10.1021/acs.langmuir.5b03946
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nanoflowers from a Wide Variety of Molecules Templated by a Hierarchical Supramolecular Scaffold

Abstract: Nanoflowers (NFs) are flowered-shaped particles with overall sizes or features in the nanoscale. Beyond their pleasing aesthetics, NFs have found a number of applications ranging from catalysis, to sensing, to drug delivery. Compared to inorganic based NFs, their organic and hybrid counterparts are relatively underdeveloped mostly because of the lack of a reliable and versatile method for their construction. We report here a method for constructing NFs from a wide variety of biologically relevant molecules (gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Carbon, elemental metals and compounds of metals with fifth and sixth group elements were the principal constituents of such assemblies. Single crystal organic nanoflowers have not been discovered so far to the best of our knowledge, though, single crystal inorganic nanoflowers 4 assemblies of organic nanoflowers 5 , 6 , hybrid organic-inorganic nanoflowers using copper (II) ions 2 , 7 diphenylalanine 8 , N,N′-diphenyl-N,N′-bis(1-naphthyl)-1,1′-biphenyl-4,4′-diamine (NPB) 9 and DNA based nanoflowers have been reported recently 10 – 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon, elemental metals and compounds of metals with fifth and sixth group elements were the principal constituents of such assemblies. Single crystal organic nanoflowers have not been discovered so far to the best of our knowledge, though, single crystal inorganic nanoflowers 4 assemblies of organic nanoflowers 5 , 6 , hybrid organic-inorganic nanoflowers using copper (II) ions 2 , 7 diphenylalanine 8 , N,N′-diphenyl-N,N′-bis(1-naphthyl)-1,1′-biphenyl-4,4′-diamine (NPB) 9 and DNA based nanoflowers have been reported recently 10 – 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the SHS particles are made from small-molecule guanosine derivatives, they offer the potential of combining the best attributes of nanovaccines with those of small-molecule immunomodulators [56, 57]. Furthermore, the fact that the SHS particles can encapsulate other biomedically relevant molecules like proteins and polysaccharides [28], expands the potential of this work to develop more elaborated vaccine formulations and related immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…G-derivative ImAG (Figure 1(a)) was synthesized and characterized as previously reported [24, 27, 28]. A solution of 0.303 mM of ImAG SGQ was warmed in a water bath at 40°C for ~3 minutes in order to promote the formation of the SHS particles and added at a final concentration of 0.1515 mM into corresponding DNA plasmid formulations (Figure 1(b)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these materials, organic-inorganic hybrid nanoflowers (HNFs) is newly developed functional material and has received considerable attention due to its distinctive physiochemical characteristics. By binding inorganic nanoparticles to organic components, HNFs show properties of simple product synthesis and high biomolecule efficiency comparing with the pure organic nanoflowers [29] and inorganic nanoflowers [30]. Since Ge et al [31] first reported the preparation of BSA-incorporated Cu 3 (PO 4 ) 2 nanoflowers, biomaterials-based HNFs have attracted increasing interest and many researches have focused on their biochemical applications of biosensing [32][33][34], biocatalysis [35][36][37], and drug delivery [38].…”
Section: Introductionmentioning
confidence: 99%